Land as production factor - Paul Metzemakers; Erik Louw (European Regional Science Association (ERSA), 2005)
To justify industrial land development, municipal planning officials frequently use the argument that unrestricted availability of business sites will foster economic development and employment growth. However, to date convincing evidence to support this claim does not exist. So empirical research into this subject is warranted. Furthermore, this relationship implicitly assumes that the acreage of land, necessary for firms to be able to conduct their business, is a production factor like labour and capital. Unfortunately, research on land use from this perspective has since long disappeared from mainstream economic theory. Ample research is done on land use in relation to firm location, both empirically and theoretically. However, the amount of land as a production factor for firms is generally disregarded. This lack of theory may hinder research into the claim made by planning officials. Therefore, present paper seeks to reintroduce land as a production factor in economic theory. In this article we explore to what extent land can be regarded as a production factor. We aim to integrate this view into established economic models from urban land economics and real estate theory. We do so at the macro and at the micro economic level. At the macro level, the available amount of industrial land could be a factor in national economic growth, just like growth of the labour force. At the micro level we consider whether the theory of individual firms' production function is able to incorporate the amount of land as production factor. We commence this paper with a historical overview of the treatment of land in economic theory, before we pursue a theoretical framework that incorporates land as a factor of production. The paper concludes with a comparison between land and the established production factors labour and capital.
Keywords: 330